Music and choral society «Snyatyn Boyan» at the beginning of the 20th century: formation and practical activity - Андрій Королько (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2020)
The article highlights the activities of the music and choral society «Sniatyn Boian» in the town of Sniatyn in the early 20th century. The society was founded in 1900. The statute of «Sniatyn Boian» is characterized. The first General Meeting of «Sniatyn Boian» took place only on November 1, 1901. The society was engaged in the organization of concert activities and musical and dramatic evenings. The repertoire of members of «Sniatyn Boian» included works by Ukrainian and foreign composers. The choir of the society performed not only in the town of Sniatyn and in other settlements of Pokuttia, but also in Bukovyna. Thus, on March 22, 1902, the choir performed in the town of Vashkivtsi on the occasion of celebrating of the work of Ukrainian writer Yurii Fedkovych (1834–1888). Funds from the concert went to the development of the affiliate of society «Rusian (Ukrainian) School» in the town of Vyzhnytsia. The society «Sniatyn Boian» took part in honoring the most famous Ukrainian composer Mykola Lysenko, who arrived in Galicia and Bukovyna in 1903 on the occasion of the 35th anniversary of his creative activity. During the jubilee celebrations in the city of Lviv on December 7-8, 1903, members of the society of «Sniatyn Boian» greeted the luminary of Ukrainian classical music with a solemn wreath and a congratulatory address. Probably, of the society of «Sniatyn Boian» performed in the city of Chernivtsi in the middle of December 1903, when Mykola Lysenko was there. In 1914, on the occasion of the centenary of Taras Shevchenko’s birth, the society of «Sniatyn Boian» together with other Ukrainian societies of the town of Sniatyn organized a festive concert. Thus, the society of «Sniatyn Boian» is the first Ukrainian professional music and choral organization in the Sniatyn region. Its members carried out intensive activities in the field of music education, promotion of Ukrainian music, acquainted the public with world masterpieces of musical art, involved a wide range of people in choral singing, held various charity events, organized anniversary concerts dedicated to leading figures of Ukrainian art and literature.